Ethics of Social Media Communication from an Islamic Perspective: A Qualitative Study of Muslim Practices in Indonesia - Munawaroh, Siti; Marlina, Nina Siti (Sekolah Tinggi Agama Islam Kuningan, 2025)
The transformation of social media has brought about significant changes in the religious communication patterns of Indonesian Muslim communities. This study aims to understand the actual practice of applying Islamic ethics in social media communication and identify the challenges faced in its application. Using a qualitative approach with in-depth interviews with 25 urban Muslim informants, this study analyzed the data using thematic analysis techniques assisted by NVivo software. The results found that principles such as tabayyun (verification of information), ukhuwah (maintaining brotherhood), prohibition of ghibah and namimah, politeness of language, and maintaining da'wah intentions are the central values in online communication. However, the implementation of these values often faces challenges in a digital culture that tends to be fast-paced, emotionally charged, and highly competitive. This research highlights the tension between the idealism of Islamic values and the reality of social media culture, underscoring the importance of strengthening community-based Islamic digital literacy. The practical implication of this research is the need for collaboration between da'wah organizations, educational institutions, and social media platforms to build a digital space that is ethical, productive, and reflects the values of Islam rahmatan lil 'alamin.